2015
DOI: 10.1590/1678-775720150125
|View full text |Cite
|
Sign up to set email alerts
|

Serum big endothelin-1 as a biomarker in oral squamous cell carcinoma patients: an analytical study

Abstract: Detection of abnormally elevated levels of molecules in patients with oral cancer may be useful in early diagnosis. These markers can be included in current Histopathology grading and in TNM staging systems of Oral Squamous Cell Carcinoma (OSCC) to make it more efficient. Several pro-angiogenic molecules have been assessed for the same reason. Endothelin-1 (ET-1) is a vasoactive peptide associated with the development and spread of many solid tumors, including Squamous Cell Carcinoma (SCC), but its utility in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…ET‐1 expression correlates with a poor prognosis in lung cancer (Boldrini et al., ). In HNSCC, several studies have identified the ET system as potential biomarkers of HNSCC progression and prognosis (Alaizari, Abdelbary, & Amin, ; Cheng et al., ; Hinsley, Hunt, Hunter, Whawell, & Lambert, 2012a; Hinsley, Kumar, Hunter, Whawell, & Lambert, 2012b; Hoffmann, Yurgel, & Campos, , ; Mankapure, Barpande, Bhavthankar, & Mandale, ). It has been demonstrated that overexpression of ET axis components has been found in HNSCC, ET‐1 can promote progression or invasion by stromal–epithelial interactions, and targeting the stromal ET system may be a novel therapeutic strategy (Hinsley et al., 2012b; McKenzie, Hinsley, Hunter, & Lambert, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ET‐1 expression correlates with a poor prognosis in lung cancer (Boldrini et al., ). In HNSCC, several studies have identified the ET system as potential biomarkers of HNSCC progression and prognosis (Alaizari, Abdelbary, & Amin, ; Cheng et al., ; Hinsley, Hunt, Hunter, Whawell, & Lambert, 2012a; Hinsley, Kumar, Hunter, Whawell, & Lambert, 2012b; Hoffmann, Yurgel, & Campos, , ; Mankapure, Barpande, Bhavthankar, & Mandale, ). It has been demonstrated that overexpression of ET axis components has been found in HNSCC, ET‐1 can promote progression or invasion by stromal–epithelial interactions, and targeting the stromal ET system may be a novel therapeutic strategy (Hinsley et al., 2012b; McKenzie, Hinsley, Hunter, & Lambert, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that overexpression of ET axis components has been found in HNSCC, ET‐1 can promote progression or invasion by stromal–epithelial interactions, and targeting the stromal ET system may be a novel therapeutic strategy (Hinsley et al., 2012b; McKenzie, Hinsley, Hunter, & Lambert, ). Big ET‐1 may be used as a diagnostic marker in OSCC; however, its use as a prognostic tool warrants more prospective studies (Mankapure et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Serum big endothelin-1 as a biomarker in oral squamous cell carcionoma patients: an analytical study [27].…”
Section: Non-invasive Diagnostic Methodsmentioning
confidence: 99%
“…Fifteen studies were classified in this topic addressing this topic [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. From these, several studies [14,15,17,[19][20][21][22][23] have indicated the need to develop other methods for the diagnosis of oral lesions equivalent to biopsy, but with lower cost and easy-to-apply.…”
Section: Non-invasive Diagnostic Methodsmentioning
confidence: 99%
“…But only a few markers can detect cancer at an early stage. The disadvantages of this method are most people have a small amount of these markers that prevents detection, the levels of these markers tend to increase when the disease progresses, some cancer patients may never have high levels of markers, and even in the presence of elevated levels, they do not always indicate cancer, as they may be related to other disorders [6,[32][33][34][35][36].…”
Section: Tumor Biomarkersmentioning
confidence: 99%